Financial integration, financial development and economic growth - De Gregorio, José (Estudios de Economía, 2016)
This paper analyzes the relationship between international financial integration and economic growth. Recent literature, surveyed in this paper, emphasizes the role of financial deepening on economic growth. Less attention has been paid, however, to the role of international financial integration in promoting a deep domestic financial market and through that channel fostering economic growth. Financial integration also permits portfolio diversification, allowing higher profitability of investment and, hence, higher rate of economic growth. Those issues are examines in this paper. In particular, after reviewing the theory and evidence, this paper analyzes empirically the relationships between financial integration and financial development, and between financial development and economic growth.